RELATIONSHIP OF ANTENATAL CARE VISIT, EMESIS GRAVIDARUM, AND DIETARY HABIT AGAINST ANEMIA IN PREGNANCY - Tuty Yanuarti; Linda Luciana Anggraeni; Sapera Damayanti; Millah Syafithrie; Hesti Yanti; Nina Ayu Larasati; Ika Putri Astuti; Siti Hadijah; Novita (The Indonesian Journal of Public Health, 2025)
Introduction: Anemia is one of the clinical conditions that can be found in many countries, particularly developing countries. The prevalence of anemia in pregnant women in Indonesia is 37.1% with the highest in rural areas, namely 37.8%, and the lowest in urban areas, 36.4%.  Multifactors can influence anemia in pregnancy. Aims: This study aimed to determine the relationship between ANC visits, emesis gravidarum, and diet on anemia in pregnant women patients. Methods: This study is a cross-sectional study. The research was conducted at the Independent Practice Place of Midwife Rabiah, AM.Keb, Sentosa Village, The District of Seberang Ulu II, Palembang City, South Sumatra Province. The independent variables in this study were ANC visits, emesis gravidarum, and diet, while the dependent variable was anemia in pregnant women. Our study used the SPSS ver.25 program. This study conducted univariate and bivariate analysis. The bivariate used chi-square test. Results: Based on the chi-square test with CI = 95% obtained p-value <0.001 (P<0.05), a significant association between dietary patterns and anemia in expectant mothers at TPMB Rabiah, Am.Keb, Sentosa Village, Sebrang Ulu District, Palembang City, South Sumatra Province, 2023. Conclusion: This study showed a significant association between Antenatal Care visits, Emesis Gravidarum, and Diet against anemia in expectant mothers, which can be used as a source of information for expectant mothers.